Impacts of Clear Cutting on Diversity of Ground Ants (Hymenoptera: Formicidae) in Pine Plantation Forest in Sukabumi Forest Management Unit, West Java - Ahmad Budiaman; Noor Farikhah Haneda; Adhiguna Indra nugraha; Frama Haikal (Institut Pertanian Bogor (IPB University), 2021)
Clear cutting is the main source of timber production of plantation forest management in Indonesia, but this activity disrupts the lives of ground ants. It is rarely known how clear cutting affects the ground ant community in the Indonesian plantation forest. The study aimed to analyze the impacts of clear cutting on the diversity of ground ants in the pine plantation forest of Sukabumi, West Java. The study compared the community structure of ground ants before clear cutting and after clear cutting. Ground ants were collected using a pitfall trap. Trapping of ground ants was carried out six days before the clear cutting and six days after the clear cutting. The ground ants were identified to the morphospecies level and classified into their functional role. The results showed that clear cutting alters the community indices of ground ants. Abundance, morphospecies composition, diversity index, richness index, and evenness index of ground ants after clear cutting was lower compared with those before clear cutting. The clear-felled area due to clear cutting provided favorable habitat for the generalist groups of ground ants, but negatively affected the predator and forager groups of ground ants. These findings can be used as an important factor in the development of environmenllyt-friendly forest harvesting systems in Indonesian plantation forests.